The Effect of Stress Management Ability and Interpersonal Skill on Occupational Performance of Accountants - Thapayom, Anucha (Executive Journal, 2020)
The purpose of this research is to examine the effect of stress management ability and interpersonal skill on occupational performance of accountants. Data were collected by using questionnaires from 192 accountants in Thailand. The statistics used to analyze is the multiple regression. The results revealed that two dimensions of stress management ability (stress tolerance and impulse control) have a significant positive association with occupational performance. Furthermore, two dimensions of interpersonal skill (empathy and interpersonal relationship) have a positive influence on occupational performance. On the other hand, social responsibility has no influence on occupational performance. Theoretical and professional contributions, conclusion and directions for future research were highlighted.